Electrotomographic studies in the Uzon caldera at Shaman geyser (Kamchatka Peninsula) - I.N. Modin; A.D. Skobelev; A.M. Valiulina; V.S. Stepchenkov (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле, 2023)
In 2020, in the caldera of Uzon volcano (Kamchatka Peninsula), electrical prospecting studies were carried out using the electrotomography method within the eastern thermal field near Shaman geyser. The geoelectric section is divided into three zones according to the level of electrical resistivity: relatively high-resistivity "cold" at the edges and relatively low resistivity «hot» in the center. The section of the “hot” zone, within which the Shaman geyser is located, is distinguished by anomalously low resistivity (less than 0.5 Ohm„m) at a depth of 5 to 20 m, which indicates the highest fracturing and fluid saturation of rocks in this location. Electrical monitoring was carried out above the geyser using the Omega-48 electrical tomography station and two cables 235 m and 47 m long. The first cable provided a survey depth of 60 m, the second one about 12 m. On the difference geoelectric sections based on the results of monitoring, four phases of the geyser operation are distinguished: filling, outpouring, spouting and steaming in the form of alternation of positive and negative anomalies of the electric field. Based on the results of areal measurements, it was possible to identify the channel channel to the geyser.